Genetic manipulation of lignocellulosic biomass for bioenergy. (December 2015) - Wang, Peng; Dudareva, Natalia; Morgan, John A; Chapple, Clint
Graphical abstract: Highlights: Lignocellulose serves as a potential resource for bioenergy. Genetic manipulation of lignification improves saccharification. Regulation of lignocellulosic synthesis occurs at multiple levels. Field trials of energy crop mutants indicate their promise in industrial applications. Abstract : Lignocellulosic biomass represents an abundant and sustainable raw material for biofuel production. The recalcitrance of biomass to degradation increases the estimated cost of biofuel production and limits its competitiveness in the market. Genetic engineering of lignin, a major recalcitrance factor, improves saccharification and thus the potential yield of biofuels. Recently, our understanding of lignification and its regulation has been advanced by new studies in various systems, all of which further enhances our ability to manipulate the biosynthesis and deposition of lignin in energy crops for producing cost-effective second generation biofuels.